Therapeutic suggestions with critically ill in palliative care - K Szilágyi, Adrienn; Kekecs, Zoltán; Varga, Katalin (Annals of Palliative Medicine; Vol 7, No 1 (January 26, 2018): Annals of Palliative Medicine (Clinical Hypnosis in Palliative Care: neural correlates, clinical, psychological and spiritual therapies), 2017)
Suggestions can be used without formal hypnosis, especially with critically ill patients, due to their spontaneous trance state. In this paper we outline data on the effectiveness of therapeutic suggestions. We interpret the possible mechanism of therapeutic suggestions in the context of stress cognition. Basic principles of formulating suggestions are discussed and some recommended versions of non-pharmacological pain control are provided. Case vignettes are given of how suggestions are used with critically ill ICU patients.